2015
DOI: 10.1177/1740774515597687
|View full text |Cite
|
Sign up to set email alerts
|

Considerations in the evaluation and determination of minimal risk in pragmatic clinical trials

Abstract: The classification system for categorizing the riskiness of a clinical trial is largely defined by the body of federal regulations known as the Common Rule (45 CFR 46, Subpart A) and by regulations governing the US Food and Drug Administration (FDA) codified in 21 CFR 50. This rule is applied according to the interpretation of institutional review boards (IRBs) charged with overseeing the research. If a clinical trial is determined by an IRB to constitute “minimal risk,” there are important practical implicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 48 publications
(54 reference statements)
1
59
0
Order By: Relevance
“…The Equal Estimated Welfare condition may be what some have in mind when they describe SCPCTs in which “[t]here are a number of such products …with substantial differences in price but without substantial differences in efficacy or side effects” 6 and “equally well-supported treatment option that falls within the standard range of care.” 9 Similarly, the Equal Probability of Allocation condition is what some commentators mentioned above may have in mind when they state: “to the extent that there is widespread practice variation, the resulting allocation of treatments will look very much like the allocation that will result from randomization.” 2, 7 …”
Section: Conditions Under Which δW=0mentioning
confidence: 99%
See 2 more Smart Citations
“…The Equal Estimated Welfare condition may be what some have in mind when they describe SCPCTs in which “[t]here are a number of such products …with substantial differences in price but without substantial differences in efficacy or side effects” 6 and “equally well-supported treatment option that falls within the standard range of care.” 9 Similarly, the Equal Probability of Allocation condition is what some commentators mentioned above may have in mind when they state: “to the extent that there is widespread practice variation, the resulting allocation of treatments will look very much like the allocation that will result from randomization.” 2, 7 …”
Section: Conditions Under Which δW=0mentioning
confidence: 99%
“…[45CFR46.111(2)] Second, research risks must be identified to meet the requirements for informed consent, both for assessing whether it could be a candidate for a waiver or alteration [45 CFR 46.116c] but also for assessing what research risks should be included among the “reasonably foreseeable” risks that must be disclosed. [45 CFR 46.116a(2)] 2, 28, 29 According to the regulations, research risks (and benefits) are “only those risks and benefits that may result from the research (as distinguished from risks and benefits of therapies subjects would receive even if not participating in the research).”[45 CFR 46.111(2)] The interpretive task, therefore, is to understand the phrase “therapies subjects would receive even if not participating in research” both in determining that a SCPCT has reasonable risks and in identifying reasonably foreseeable risks relevant to informed consent (and waiver or alteration) requirements. Should it be a random patient perspective or a specific patient perspective?…”
Section: Implications Of the Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Low risk pragmatic RCTs pose no or minimal incremental risk compared with usual clinical care5 and are typically head to head comparisons of medicines that are routinely prescribed according to their marketing authorisations. There are several approaches to conducting low risk pragmatic RCTs of medicines.…”
Section: Low Risk Pragmatic Rctsmentioning
confidence: 99%
“…Yet, there is considerable debate over whether standard-of-care research can be categorized as minimal risk (4). Even more controversial is the possibility of categorizing standard-of-care research in the emergency setting as minimal risk.…”
Section: Introductionmentioning
confidence: 99%